Cross-reactivity between antigens from Amblyomma cajennense and A. hebraeum (Acari: Ixodidae) - Hlatshwayo, M.; Szaboó, M. J.P.; Bechara, G. H.; Mbati, P. A. (South African Vet Assn, 2004)
Laboratory animals exposed to feeding ticks develop resistance which is reflected by a decline in tick engorgement weight, egg-laying by adults and reduced egg viability. Serum antibodies from these hosts and their reaction with tick antigens have been detected by different methods, including precipitation techniques, immunofluorescent techniques, ELISA and Western blots. However, little is known about the effects of antibodies on ticks that engorge on resistant hosts, or which tissues of the tick body are possibly immunogenic. Some researchers, using immunohistochemistry, have detected host antibodies in the gut, salivary glands and haemolymph of ticks engorged on resistant animals. The same technique has helped considerably in determining antigenic sites or antibody target in other arthropods. Consequently, immunohistochemistry techniques were used in this study to detect cross-reactivity between sera raised against Amblyomma cajennense (Fabricius, 1787) with Amblyomma hebraeum (Koch, 1844), and vice versa. The results show the existence of shared antigens between the 2 tick species. In general, our results point more to a 1-way cross-reactivity of A. hebraeum with A. cajennense than a reciprocal cross-reactivity, suggesting that A. hebraeum is more immunogenic than A. cajennense.
Keywords: Amblyomma cajennense; Amblyomma hebraeum; Antigens; Cross-reactivity